PENYUSUNAN DESAIN TATA KELOLA BUMDES DI DESA SUMBERSEKAR KECAMATAN DAU KABUPATEN MALANG - Mudrifah Mudrifah; Aviani Widyastuti (Universitas Muhammadiyah Malang, 2020)
Sumbersekar Village also participated in running a government program by forming the Sumbersekar BUMDES. The fund for the formation and management of BUMDES itself is obtained from the Village Fund Allocation The village fund provided by the state aims to make villages more productive. Increased productivity of the village is seen from the economic development increases, the level of people who work and have increased business, the quality of life including health becomes better. The purpose of the dedication is to provide assistance to the village officials of Sumbersekar in designing the BUMDES governance that will be established so that it can run in accordance with the vision and mission of the Village. Through the establishment of BUMDES, it is hoped that the economy of the Sumbersekar village community can improve from before. Because with the BUMDES, the business units in the village will be better managed. Therefore, a clear organizational structure and division of tasks is needed at the beginning of the establishment of the BUMDES so that at the time the implementation can proceed in accordance with the established governance system.Keywords: Governance design, BUMDes, Sumbersekar Village